PENGELOLAAN LINGKUNGAN HIDUP MENURUT PERSPEKTIF FIQIH - YUNITA YUNITA; Zahratul Idami (Fakultas Hukum, Universitas Samudra, 2020)
Islam prohibits human beings from destructing the environment which can provide detrimental effects on their lives and other creatures. The primary sources of Islamic teachings are Al Qur’an and Al Hadist as well as ijtihad (Fiqh). Fiqh as an Islamic jurisprudence is applied based on the development of the community in the context which derives from the authentic dalils from Islamic sources. In the Fiqh, so-called Fiqh Siyasah, the government plays a vital role in designing policy to align with and capitalize on environmental sustainability. So does Fiqh of the environment. It describes how Islam governs environmental management, so that it can be maintained and preserved from the destruction which can be harmful to human beings and other creatures in this world. This article aims to elaborate some Islamic principles concerning the guidance of environmental management issues which have to be followed by human beings to preserve their dignity and integrity as well as to protect nature and other creatures as a sign that they are indeed the best creation of all.